2012
DOI: 10.1016/j.talanta.2012.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lead in medicinal plants by high-resolution continuum source graphite furnace atomic absorption spectrometry using direct solid sampling

Abstract: A procedure is proposed for Pb determination in medicinal plants by high-resolution continuum source graphite furnace atomic absorption spectrometry (HR-CS GF AAS) using direct solid sampling. Among Pd(NO(3))(2), Pd/Mg(NO(3))(2), NH(4)H(2)PO(4) and the W-coated platform tested as chemical modifiers, Pd(NO(3))(2) presented the best performance. Calibration plots (10-1000 pg Pb) with regression coefficients better than 0.999 were typically obtained. Accuracy was checked for Pb determination in five plant certifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…By using HR-ICP-MS, Pb was determined in 95 dietary supplements with concentrations in the range 20-48600 μg kg −1 [7]. Recently, Pb was determined in medicinal plants by high-resolution continuum source (HR-CS) GF AAS using direct solid sampling [17]. The authors reported agreement between their data and reference values at a 95% confidence level.…”
Section: Leadmentioning
confidence: 88%
“…By using HR-ICP-MS, Pb was determined in 95 dietary supplements with concentrations in the range 20-48600 μg kg −1 [7]. Recently, Pb was determined in medicinal plants by high-resolution continuum source (HR-CS) GF AAS using direct solid sampling [17]. The authors reported agreement between their data and reference values at a 95% confidence level.…”
Section: Leadmentioning
confidence: 88%
“…All glasswares used in this experiment were soaked in 10% nitric acid for 24 h, then rinsed completely with double distilled water, and dried in an oven before use. Concentrations of Pb in the samples were determined at wavelength of 283.8 nm for Pb (Figuerêdo Rêgo et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Guo et al 36 tackled these analytical challenges by developing a method using mixed plasma gas ICP-DRC-MS. The use of CH 4 as reaction gas eliminated the spectral interference from 40 Ar 2 + , whilst the mixed CH 4 -Ar plasma gas reduced minor interferences from 63 Cu 16 OH + , 64 Zn 16 O + and 64 Cu 16 O + hydroxide and oxide ions by more than 50%. Furthermore presence of C in the plasma gas also improved Se ionisation to give a three-fold improvement in sensitivity.…”
Section: Rare Earth Elementsmentioning
confidence: 99%
“…While ICP-MS might be the usual analytical technique to determine trace elements in these samples, various other approaches are sometimes employed. A method to measure Pb concentrations in medicinal plants, using slurry sampling and HR-CS-ETAAS, was reported by Rego et al 64 Various modiers were tested and the best performance was given with Pd(NO 3 ) 2 . Lead contents of various medicinal plants samples were in the range 0.30-1.94 mg g À1 .…”
Section: Rare Earth Elementsmentioning
confidence: 99%